2006
DOI: 10.4067/s0717-95022006000300013
|View full text |Cite
|
Sign up to set email alerts
|

Complete Ossification of the Superior Transverse Scapular Ligament in an Indian Male Adult

Abstract: SUMMARY:Complete ossification of the superior transverse scapular ligament is generally considered to be rare and has not been previously described in an Indian. In the diagnosis of suprascapular nerve entrapment syndrome, variations in the anatomy of the superior transverse scapular ligament must be considered as possible etiologic factor, as illustrated by this case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 5 publications
1
21
0
2
Order By: Relevance
“…SN entrapment). (13) The various shapes and sizes of the SSN may also play a role in SN entrapment, (14) as narrow SSNs have been found in patients with SN entrapment. (15) While previous studies have classified the shapes of SSN using certain mathematical formulas, (8,12,15) in this study, we used a simple and reproducible classification system (12) to document the various types of SSN.…”
Section: Discussionmentioning
confidence: 99%
“…SN entrapment). (13) The various shapes and sizes of the SSN may also play a role in SN entrapment, (14) as narrow SSNs have been found in patients with SN entrapment. (15) While previous studies have classified the shapes of SSN using certain mathematical formulas, (8,12,15) in this study, we used a simple and reproducible classification system (12) to document the various types of SSN.…”
Section: Discussionmentioning
confidence: 99%
“…Variations on STSL have been reported by Testut (1904) and Poirier & Charpy (1911). Calcification, partial or complete ossification and multiple bands were also discussed by Ticker et al, (1998) and related by others authors (Osuagwu et al, 2005;Khan). Moreover, others studies have been observed the prevalence of these variations (Kajava, 1924;Vallois,1925;Vallois, 1926;Gray, 1942;Lewis, 1959).…”
Section: Introductionmentioning
confidence: 96%
“…The suprascapular notch is roofed by the superior transverse scapular ligament (STSL) converting it into foramen in some species (Khan, 2006). In humans, this conversion is a result of the ossification of the STSL (Gardner et al, 1988;Bergman et al, 1988, Williams et al, 1989.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies in United States, the incidence of complete ossification of STSL were found 3.7%, 4% and 5%, respectively [11,12,43,47,49]. There was also only one complete ossification of STSL in Indian scapulae in one study [22].…”
Section: Discussionmentioning
confidence: 99%